Additive multiple predator effects can reduce mosquito populations. (2nd August 2019) - Cuthbert, Ross N.; Callaghan, Amanda; Sentis, Arnaud; Dalal, Arpita; Dick, Jaimie T. A.
Abstract : 1. Multiple predator interactions may profoundly alter ecological community dynamics and can complicate predictions of simpler pairwise predator–prey interaction strengths. In particular, multiple predator effects may lessen or enhance prey risk, with implications for community‐level stability. Such emergent effects may modulate natural enemy efficacy towards target organisms. 2. In the present study, a functional response approach was used to quantify emergent multiple predator effects among natural enemies towards the disease vector mosquito complex, Culex pipiens . Conspecific multiple predator–predator interactions of the cyclopoid copepod Macrocyclops albidus (intermediate predator) were quantified by comparing multiple predator consumption simulations, based on individual consumption rates, with multiple predator consumption rates that were experimentally observed. Further, the study examined the influence of the presence of a predator at a higher trophic level, Chaoborus flavicans, on copepod group predation. 3. Both predators displayed type II functional responses, with C. flavicans consuming significantly more prey than M. albidus individually. Overall consumption levels of mosquitoes increased with greater predator density and richness. Antagonistic or synergistic emergent multiple predator effects between conspecifics of M. albidus were not detected, and the higher‐level predator did not reduce effects of the intermediate predator. Accordingly, evidence for additive multiple predator interactions was found. 4. The lack of predator–predator interference between cyclopoid copepods and larval chaoborid midges provides strong support for their combined application in mosquito biocontrol. It is proposed that there should be increased examination of multiple predator effects in assessments of natural enemy efficacies to better understand overall predatory effects within communities and utilities in vector control. Abstract : Larval chaoborid midge Chaoborus flavicans consumed significantly more larval Culex pipiens mosquito prey than did cyclopoid copepod Macrocyclops albidus . Multiple copepod predator consumption rates towards larval mosquitoes combined additively, irrespective of the presence of the higher‐order chaoborid predator. A lack of predator–predator interference may enhance the predatory effects of natural enemies on medically important mosquito prey.